Sharia Economic Literacy and Trust: Path Analysis of Preferences for Using Sharia Finansial Products in the Digital Era - Alfian, Ian; Surya Agustina (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
As of June 2023, Indonesia's Islamic banking market share was only 7.3% of the global banking industry, despite the country having the largest Muslim population in the world. Only around 6.9% of all national banking assets will be Islamic banking assets by the end of 2023, according to data from the Financial Services Authority (OJK). With trust acting as an intermediary variable, the purpose of this study is to examine how people's preferences for utilizing Islamic banks are impacted by their level of Islamic economic literacy. The findings indicated that trust (t-count 21.247 > t-table 1.660; sig. 0.000) and people's preferences for utilizing Islamic banks (t-count 3.291 > t-table 1.660; sig. 0.000) are positively and significantly impacted by Islamic economic literacy. Preference is significantly impacted by trust as well (t-count 2.736 > t-table 1.660; sig. 0.003). Additionally, using trust as an intervening variable, Islamic economic literacy significantly influences preferences (t-count 2.694 > t-table 1.660; sig. 0.020). In order to increase the penetration of Islamic banks in Indonesia (OJK), this study highlights the significance of raising public literacy and trust.